2020
DOI: 10.3390/nu12092554
|View full text |Cite
|
Sign up to set email alerts
|

Inputs to Thirst and Drinking during Water Restriction and Rehydration

Abstract: Current models of afferent inputs to the brain, which influence body water volume and concentration via thirst and drinking behavior, have not adequately described the interactions of subconscious homeostatic regulatory responses with conscious perceptions. The purpose of this investigation was to observe the interactions of hydration change indices (i.e., plasma osmolality, body mass loss) with perceptual ratings (i.e., thirst, mouth dryness, stomach emptiness) in 18 free-living, healthy adult men (age, 23 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
0
22
0
9
Order By: Relevance
“…Thirst intensity, assessed using the category and visual analog scales, was used to evaluate the subjective sensation of the fluid status of healthy individuals in daily life [ 27 , 28 ]. According to Davies et al [ 29 ], changes in body weight can be used to estimate body fluid status in ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thirst intensity, assessed using the category and visual analog scales, was used to evaluate the subjective sensation of the fluid status of healthy individuals in daily life [ 27 , 28 ]. According to Davies et al [ 29 ], changes in body weight can be used to estimate body fluid status in ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior work has indicated that during free access to water, rather than in response to water challenges, body‐fluid variables like plasma osmolality and angiotensin II concentrations did not relate to thirst perceptions but rather were influenced by anticipatory thirst as well as surrounding eating (Phillips, Rolls, Ledingham, & Morton, 1984). Recent experimental work has demonstrated that after rehydration following water restriction, Posm was dissociated with thirst ratings which suggests that thirst is more perceptual and not as directly tied to hydration status during ad libitum water drinking (Armstrong, Giersch, Dunn, et al, 2020). Those findings parallel our own that hydration as measured via Usg during an ad libitum state in extreme thermal environments were not associated with thirst perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the phrase dynamic complexity applies to the vast, integrated, brain-wide network of nerve circuits and brain regions that regulate thirst, drinking, body water volume, and fluid concentration [ 92 ]. The findings of two recent human studies [ 93 , 94 ] suggest that thirst is one of multiple conscious perceptions and subconscious autonomic responses ( Figure 4 ) that evolve simultaneously during dehydration and rehydration to influence drinking behavior. Simply stated, the internal motivation to consume water is influenced by multiple factors that reinforce the perception of thirst.…”
Section: The Complexity Of Thirst and Drinkingmentioning
confidence: 99%
“…These sensory signals (e.g., mouth dryness, swallowing fluid) rapidly reduce and limit fluid intake by modulating satiety and opposing overdrinking [ 115 ]. Thus, whenever fluid is consumed, even if the volume is small, oropharyngeal signals diminish the sensation of thirst [ 93 , 115 ] and theoretically reduce the risk of EHN by reducing fluid intake.…”
Section: Rehydration Optionsmentioning
confidence: 99%